Sport Team Board App As A Study Media In Applying The Pjbl Model In Futsal Course - permadi, Andes; Ilahi, Bogy Restu; Rizky, Oddie Barnanda (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2024)
This study aims to improve the quality of learning in the Futsal practicum course using the Sport Team Board App as a learning media in the application of the PjBL model for Physical Education Study Program students at FKIP Bengkulu University. Learning media in the digital era must be aligned with technological developments, besides that learning media must be interesting, creative, and in accordance with current learning needs. Researchers chose this application because the Sport Team Board App is an application that meets the previously mentioned criteria to be used as a special learning media for practicum in meeting the demands of learning outcomes. This research uses descriptive qualitative, where the practice of adopting the Sport Team Board App-based PjBL learning approach is described in each context. Where data collection is done through test and non-test techniques. As a result, the target achievement was obtained in cycle II with the following details; 15 students or 42% obtained category A, 17 students or 47% obtained category B, 4 students or 11% obtained category C, and none or 0 students obtained category D. The results of the response questionnaire distributed to students showed a final score of 24.61 or an average of 4.1 which means that the category most chosen by students is agree. The results of the response questionnaire distributed to students show the final score of 24.61 or an average of 4.1, which means that the category most chosen by students is agree. These results indicate that the implementation of learning in the application of PjBL for VI semester students of the Physical Education Study Program at FKIP Bengkulu University is of interest to students. It not only reaches the aspect of knowledge implementation but also increases student creativity and interest in learning activities.